Pengembangan Produk Sambal Berbahan Dasar Cumi-Cumi (Loligo sp.) - Gunibala, Miston; Yusuf, Nikmawatisusanti; Mile, Lukman (Jambura Fish Processing Journal, 2024)
Sambal is a type of food accompaniment that is well known in Asia, especially Indonesia and is popular with the public. This study aims to obtain the right formula for chili products made from squid (Loligo sp). The treatment used in this study was the composition of squid with 4 treatment levels, namely 0 gr (control), 70 gr, 80 gr, 90 gr. The parameters tested included testing for protein content, moisture content, ash content and hedonic organoleptic tests. This study was designed using a completely randomized design (CRD) non factorial. Chemical data analysis was tested using ANOVA and further tested by Duncan, hedonic organoleptic data was designed with Kruskal-wallis and further tested by Duncan. The results showed that the squid formulation had a significant effect (p0.05) on all hedonic proximate and organoleptic test parameters. The addition of squid had a significant effect on the water content with values ranging from 0.06% -42.95%, ash content 1.52% -1.87%, protein content 5.06% -9.95%. Hedonic analysis results for taste 2.72-4.47, color 3.80-4.64, aroma 3.96-4.52.